2006
DOI: 10.1037/0096-3445.135.2.298
|View full text |Cite
|
Sign up to set email alerts
|

Is the binding of visual features in working memory resource-demanding?

Abstract: The episodic buffer component of working memory is assumed to play a role in the binding of features into chunks. A series of experiments compared memory for arrays of colors or shapes with memory for bound combinations of these features. Demanding concurrent verbal tasks were used to investigate the role of general attentional processes, producing load effects that were no greater on memory for feature combinations than for the features themselves. However, the binding condition was significantly less accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

76
585
14
32

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 434 publications
(707 citation statements)
references
References 47 publications
76
585
14
32
Order By: Relevance
“…The first is that, to the extent that a post-stimulus suffix passes the external attentional filter, it will interfere with memory and will do so more for recent items. This would be consistent with empirical evidence that the recency effect observed by Allen et al (2006) and others reflects cumulative retroactive interference on earlier items from subsequent items, the final item being entirely free from such interference. When a post-stimulus suffix is presented it will generate additional retroactive interference and this will be greater the more recent the item, resulting in a reduced recency effect.…”
Section: Insert Figure 1 Heresupporting
confidence: 89%
“…The first is that, to the extent that a post-stimulus suffix passes the external attentional filter, it will interfere with memory and will do so more for recent items. This would be consistent with empirical evidence that the recency effect observed by Allen et al (2006) and others reflects cumulative retroactive interference on earlier items from subsequent items, the final item being entirely free from such interference. When a post-stimulus suffix is presented it will generate additional retroactive interference and this will be greater the more recent the item, resulting in a reduced recency effect.…”
Section: Insert Figure 1 Heresupporting
confidence: 89%
“…Allen, Baddeley, & Hitch, 2006, 2014. This extends limited previous work with children using different visual stimuli (Burnett Heyes et al, 2012;Hitch et al 1988;Pickering et al 1998) to the current task and stimulus sets.…”
Section: Discussionsupporting
confidence: 70%
“…According to this principle, it is very reasonable to accept that fewer objects than single features can be maintained. Our results concerning memory for cross-domain associations were more in line with Allen et al (2006) and Cowan et al (2012) for within-domain combinations and revealed a lower capacity for objects than single features. Cowan et al's idea of chunk decomposition could explain the results obtained in the present study and as such apply to the maintenance capacity limit of the episodic buffer.…”
Section: Discussionsupporting
confidence: 71%
“…Two domains were investigated: the binding of visuospatial features into objects and of words in the comprehension and retention of prose. In the visuospatial domain, Allen et al (2006) assessed through probe recognition the retention of either isolated features such as shapes or colors or combinations of these features into integrated objects. In the former condition, participants were asked whether the probed color or shape was present in an original array of four shapes or four colors (i.e., individual feature conditions), whereas in the latter, they judged whether the probed feature combination had been present in an original set of four colored shapes, requiring a binding of the constituent features (i.e., binding condition).…”
Section: The Episodic Buffer and The Binding Processmentioning
confidence: 99%